Explaining FOMO Symptoms Based on Maladaptive Perfectionism and Emotional Loneliness with Emphasis on the Mediating Role of Artificial Intelligence Dependency among Female High School Adolescents - Rajabzade Dezfuli, Zohre; Moshtaghi, Saeed; NooriSamarein, Shahram (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to explain FOMO (Fear of Missing Out) symptoms based on maladaptive perfectionism and emotional loneliness, with a particular focus on the mediating role of artificial intelligence dependency among female high school adolescents. Methods and Materials: This correlational study employed a structural equation modeling approach to investigate the relationships among maladaptive perfectionism, emotional loneliness, artificial intelligence dependency, and FOMO symptoms. The statistical population consisted of all female students enrolled in secondary high schools in Dezful, Iran, during the 2025–2026 academic year. A total of 250 students were selected through convenience sampling. Data were collected using the Fear of Missing Out Scale developed by Przybylski et al. (2013), the Multidimensional Perfectionism Questionnaire by Hewitt and Flett (2004), the Social and Emotional Loneliness Scale by DiTommaso et al. (2004), and the Artificial Intelligence Dependency Questionnaire developed by Huang et al. (2024). Data analysis was conducted using descriptive and inferential statistics in SPSS and AMOS software packages. Path analysis and structural equation modeling were utilized to evaluate both direct and indirect relationships among the study variables and to assess the overall model fit. Findings: The results demonstrated that maladaptive perfectionism and emotional loneliness significantly predicted FOMO symptoms both directly and indirectly through artificial intelligence dependency. Maladaptive perfectionism showed a significant positive effect on artificial intelligence dependency (β = 0.411, p < .01), while emotional loneliness also exhibited a significant positive effect on artificial intelligence dependency (β = 0.506, p < .01). Furthermore, maladaptive perfectionism had a significant direct effect on FOMO symptoms (β = 0.267, p < .01) and a significant indirect effect through artificial intelligence dependency (β = 0.124, p < .01). Similarly, emotional loneliness exerted a significant direct effect on FOMO symptoms (β = 0.259, p < .01) and a significant indirect effect mediated by artificial intelligence dependency (β = 0.152, p < .01). Artificial intelligence dependency itself significantly and positively predicted FOMO symptoms (β = 0.301, p < .01). Model fit indices indicated a satisfactory fit of the proposed structural model to the observed data. Conclusion: The findings suggest that adolescents with higher levels of maladaptive perfectionism and emotional loneliness are more likely to develop dependency on artificial intelligence technologies, which in turn intensifies FOMO symptoms. Artificial intelligence dependency functions as a significant psychological mechanism linking individual vulnerabilities and social-emotional difficulties to heightened fear of missing out. These results highlight the importance of addressing maladaptive perfectionistic standards, strengthening real-world emotional relationships, and promoting healthy patterns of AI use in interventions designed to reduce FOMO among adolescents.